Legal Protection Of Patent Right Holders In Efforts To Develop Economic Aspects - Suwardi, Suwardi (MARAS : Jurnal Penelitian Multidisiplin, 2024)
The function and role of patents faces quite serious obstacles considering that they are so important in supporting economic development. Development based on technology is absolutely necessary to support successful development in the economic sector to support success in the technological sector. Legal instruments are needed that regulate legal protection if an invention in the field of technology is misused by someone else who has no right to use it. Legal instrument Number 6 of 1998 as amended and perfected by Law Number 14 of 2001 (hereinafter abbreviated to the Patent Law / UUP). The number of patent applications originating from within the country was 229 or 1.82 percent of all patent applications. Meanwhile, the number of simple patent applications originating from within the country was 153 or 41.02 percent of all simple patent applications. What is the legal protection for patent holders in economic aspects ? The method used in this writing is normative which refers to legal norms and existing laws, namely Law Number 14 of 2001 concerning patents. Patent studies for holders will be able to provide protection for apprentices and business actors who are still hampered by the influence of the Covid-19 pandemic so that maximum service is hampered, as well as our bureaucratic system which is not yet impartial to business actors, so there needs to be a commitment to togetherness between business actors and The bureaucratic system must be synergistic in helping each other and providing opportunities for each other so that patent ownership can achieve the mutually expected targets. Conditions that must be prepared are factors that trigger successful ownership of patent rights for rights owners based on a sustainable economy.